2021
DOI: 10.3390/brainsci11040523
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Depressive Symptoms through the Lens of Sexual Orientation

Abstract: This research seeks to explore the impact of COVID-19 on depressive symptoms, analyzing discrepancies of sexual orientation in a Portuguese-speaking sample. 1590 individuals participated, of which 63% were women, and 88% self-identified as straight. Participants responded to the depression sub-scale of the Beck Symptoms Iventory-18, the fear of COVID-19 scale and the COVID-19 negative impact scale. Depressive symptoms observed were higher than expected, and several significant differences were obtained: women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 78 publications
1
4
0
4
Order By: Relevance
“…These psychosocial circumstances may have increased the existing vulnerabilities of this population. Our study confirms previous data from Portugal and Brazil 70,71 concerning the impact of COVID-19 among LGBTIQ population on mental health and work-related quality of life, and this may have conditioned the access to health care services, through the anticipation of rejection and fear of the disease. On the other hand, the fact that many families do not accept their LGBTIQ family members, led many of our participants to go back into the closet, and this is not without relevant psychosocial consequences, such as LGBTIQ identity erasure on the existing heteronormative culture and exposure to sexual stigma.…”
Section: Lgbtiq Topicssupporting
confidence: 90%
“…These psychosocial circumstances may have increased the existing vulnerabilities of this population. Our study confirms previous data from Portugal and Brazil 70,71 concerning the impact of COVID-19 among LGBTIQ population on mental health and work-related quality of life, and this may have conditioned the access to health care services, through the anticipation of rejection and fear of the disease. On the other hand, the fact that many families do not accept their LGBTIQ family members, led many of our participants to go back into the closet, and this is not without relevant psychosocial consequences, such as LGBTIQ identity erasure on the existing heteronormative culture and exposure to sexual stigma.…”
Section: Lgbtiq Topicssupporting
confidence: 90%
“…Recent research has indicated that members of sexual minority groups have suffered a high psychological impact from the crisis (23)(24)(25)(26)(27)(28)(29)(30)(31), but these studies were done in samples of sexual minority people only and, therefore, that impact cannot be compared with the psychological impact suffered by the heterosexual people also affected by the crisis (32). Seven studies with online recruited convenience samples from the United States of America (9,(33)(34)(35)(36)(37)(38) and one online study conducted in Portugal and Brazil (39) comparing sexual minorities and heterosexual persons found that the psychological impacts among members of sexual minorities were greater. A prospective cohort study in Southern California also found that sexual minorities reported more negative coping strategies with respect to the COVID-19 crisis compared to heterosexual individuals (40).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies observed that sexual minorities, in general, presented worse mental health than the heterosexual population during lockdown ( Duarte & Pereira, 2021 ; Liu et al, 2022 ). In our study, we focused only on women and it seems that the differences are less clear, since no statistically significant differences were observed.…”
Section: Discussionmentioning
confidence: 93%